1977
DOI: 10.1007/bf01541154
|View full text |Cite
|
Sign up to set email alerts
|

Sexual daydreams and quantitative aspects of sexual activity: Some relations for males across adulthood

Abstract: Sexual daydreams were measured using the Imaginal Processes Inventory, while retrospective data on number of coital partners, frequency of intercourse in early marriage, and quantity of sexual activity experienced between 20 and 40 years of age were obtained by interview. The 277 men studied ranged from 24 to 91 years. The frequency and intensity of sexual daydreams declined with increasing age, and after age 65 virtually disappeared. The occurrence of sexual daydreams varied directly with each of the three be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 6 publications
1
6
0
1
Order By: Relevance
“…Males with the highest cumulative lifetime number of paraphilias and paraphiliarelated disorders (5 or more), however, self-reported a higher current TSO/week (mean 10 orgasms/week) and increased time consumed by PA and/or PRD-associated sexual fantasies, urges, and behaviors (mean 2-4 h/day). Other investigators have also reported a positive correlation between the frequency of sexual fantasy, masturbation, number of lifetime sexual partners, and self-rated sexual drive (Giambra & Martin, 1977;Laumann et al, 1994;Wilson & Lang, 1981).…”
Section: Sexual Desire Dysregulationmentioning
confidence: 93%
“…Males with the highest cumulative lifetime number of paraphilias and paraphiliarelated disorders (5 or more), however, self-reported a higher current TSO/week (mean 10 orgasms/week) and increased time consumed by PA and/or PRD-associated sexual fantasies, urges, and behaviors (mean 2-4 h/day). Other investigators have also reported a positive correlation between the frequency of sexual fantasy, masturbation, number of lifetime sexual partners, and self-rated sexual drive (Giambra & Martin, 1977;Laumann et al, 1994;Wilson & Lang, 1981).…”
Section: Sexual Desire Dysregulationmentioning
confidence: 93%
“…Those with the most active sex lives seem to have the most sexual fantasies, and not vice versa. Several studies have shown that frequency of fantasy is positively correlated with masturbation frequency, intercourse frequency, number of lifetime sexual partners, and self-rated sex drive (Crepault et al, 1976;Giambra & Martin, 1977; G. D. Wilson & Lang, 1981). In addition, Streissguth, Wagner, and Wechsler (1969) found that hospitalized men deprived of sexual activity with partners had lower sexual fantasy scores than comparable outpatient and nonpatient samples, even though the groups did not differ on overall daydreaming frequency.…”
Section: Sexual Satisfactionmentioning
confidence: 94%
“…On this scale, the erotic content alludes to the individual's daydreams. It has shown a high internal consistency (Giambra, 1977(Giambra, , 1980Singer & Antrobus, 1972), and its scores have been associated with distinct sexual indicators (Giambra, 1983a(Giambra, , 1983bGiambra & Martin, 1977). The MSFQ includes subscales for genital fantasies, having sex in public, sensuality, dominance-submission, and sexual aggression; these five dimensions were established through principalcomponents factor analysis of the ratings provided by heterosexual students (Smith & Over, 1991) that showed alpha values of internal consistency between .93 and .86.…”
Section: Measurement Of Sex Fantasiesmentioning
confidence: 99%